Role of Clinical Features and GeneXpert MTB/RIF Assay in Diagnosing Tuberculosis Among Toddler Patients in Surabaya - Prasanti, Siva Allysha; Setiabudi, Rebekah Juniati; Setyoningrum, Retno Asih; Purwanto, Satiti Palupi (Indonesian Journal of Tropical and Infectious Disease, 2025)
Tuberculosis (TB) is a leading cause of global morbidity and mortality, mainly in the age of 0-5 years old (toddlers). Several risk factors make toddlers more prone to TB infection. Although it commonly depends on clinical evidence, diagnosis of toddler TB can be done using microbiological confirmation like GeneXpert MTB/RIF Assay. However, this is still challenging to perform due to the low bacterial loads and difficulties in obtaining specimens. While prior studies focused more on the clinical aspects, this study will determine both the clinical and microbiological profiles of toddler TB patients at Dr. Soetomo General Academic Hospital Surabaya. This study was conducted using a retrospective approach. Samples were obtained using a total sampling technique from electronic medical records from January 2018 to September 2023. Variables collected include age, gender, type of TB, BCG vaccination status, history of household contact, nutritional status, symptoms, and GeneXpert MTB/RIF examination specimens and results. Among 125 toddler TB patients, the majority being female (57%), between the ages of 1–2 (45%), had BCG vaccination (86%), and without a history of household contact (63%). Most of the samples were malnourished (56%) and had cough as the symptom (62%). In GeneXpert MTB/RIF examination, gastric aspirate was the most collected specimen (52%) and the most common result found was negative (70%). In addition, two toddler patients were found to have DR-TB. In conclusion, while GeneXpert MTB/RIF assay predominantly resulted in negative, clinical features become the essential evidence to establish a diagnosis of tuberculosis among toddler patients.